IDENTIFIKASI KESULITAN GURU PENDIDIKAN SEJARAH DALAM MELAKSANAKAN PEMBELAJARAN KURIKULUM 2013 PADA SMAN 1 KEUMALA KABUPATEN PIDIE - Muslem, Muslem; Fajri, Heri (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2023)
This research is entitled Identification of Difficulties for History Education Teachers in Implementing Learning Through the 2013 Curriculum at SMAN 1 Keumala, Pidie Regency. The problem in this research is the teacher's difficulties in planning, implementing, assessing learning through the 2013 curriculum. This study aims to find out how difficult it is for teachers to implement learning through the 2013 curriculum at SMAN 1 Keumala, Pidie Regency. The informants of this study were all 5 teachers of History Education at SMAN 1 Keumala, Pidie Regency. The method used is descriptive analysis with the approach used in this research is a qualitative approach. Data collection was carried out using a questionnaire. Data analysis was performed by calculating percentages and simple averages. The results showed that the teacher's level of difficulty in planning learning through the 2013 curriculum obtained an average score of 3.11 and was included in the medium category. Then the teacher's level of difficulty in carrying out learning based on the 2013 curriculum, obtained an average score of 3.19 and is included in the medium category. Meanwhile, the teacher's level of difficulty in learning assessment based on the 2013 curriculum, obtained an average score of 2.93 and is included in the medium category. Because the percentage of difficult answer choices at the assessment stage is higher than the other stages, the assessment stage is the most difficult stage in learning based on the 2013 curriculum.Keywords : Difficulties of History Education Teachers, Curriculum 2013